The shopping activities in Melaka UNESCO World Heritage site: is the local community benefited? - Ab Rahman, Syakir Amir; Mahamod, Lukman Hakim; Jaafar, Samsuddin (Kolej Universiti Islam Antarbangsa Selangor, 2018)
Tourism is a significant sector to boost the local economic development with its strength to offer the economic sources to the destination. However, to date, there has been discussion on the on local economic in cultural heritage in Malaysia. This study examined tourists’ expenditure on shopping sector, and its contribution to the local economic in Melaka UNESCO World Heritage area. A total of 1000 questionnaire survey were collected. Inferential analysis was used to identify the expenditure pattern of domestic and international tourist and its contribution to the local economy. The results revealed that the shopping sector recorded the third highest expenditure and were benefited to the local economy.